A study of comminution-liberation and floatability of Copper from printed circuit boards (PCBs) scrap - Aimi Noorliyana, Hashim; Mohd Zaheruddin, Kasmuin; Md Fazlul, Bari; Sri Asliza, Md Amin; Kamarudin, Hussin (Universiti Kebangsaan Malaysia (UKM), 2009)
Organized by Universiti Kebangsaan Malaysia (UKM), 3rd - 4th December 2008 at Danau Golf Club, Bangi, Selangor.